Penaklukan Konstantinopel: Strategi Militer Sultan Muhammad Al-Fatih (1453-1481 M) - Sumarni, Titin; Husni, Muhammad; Santi, Selvia (Faculty Ushuluddin, Adab, and Dakwah Institut Agama Islam Negeri (IAIN) Palangka Raya, 2025)
The issues discussed in this study are: 1) how is the general description of the Ottoman Dynasty. 2) how was the military strategy of Sultan Muhammad Al-Fatih in the conquest of Constantinople. 3) how is the life history of Sultan Muhammad AlFatih. The objectives of this research are: 1) to know the general description of Constantinople. 2) to know the life history of Sultan Muhammad Al-Fatih. 3) to know the military strategy of Sultan Muhammad Al-Fatih in conquering Constantinople. This research is a qualitative historiographic research, with the type of library research. The data sources used in this research are primary and secondary data obtained from books, journals, and other works. The method used in this research is the historical method which is divided into four stages, namely, heuristics, verification, interpretation and historiography. Meanwhile, the method used in this research is the theory of military strategy. The results of this study show that: 1) the general description of the Ottoman Dynasty includes, geographical conditions, religious conditions, military conditions, social conditions and political conditions. 2) Sultan Muhammad Al-Fatih’s life history starts from his birth and childhood, achievements, death, personality and military policy. 3) Sultan Muhammad Al-Fatih’s military strategy used three components of military strategy when conquering Constantinople. The three components of the military strategy: First, the purpose of Sultan Muhammad Al-Fatih to conquer Constantinople. Second, the way Sultan Muhammad Al-Fatih Conquered Constantinople. And, thirdly, the means by which Sultan Muhammad Al-Fatih and his troops conquered Constantinople. Because of his unanimous goal, his unexpected way of attacking the opponent and adequate means to conquer the enemy. Because of the strength of the three components of military strategy owned by Sultan Muhammad AlFatih, then on 29 May 1453 Constantinople could be conquered by Sultan Muhammad Al-Fatih.